2008
DOI: 10.1007/s00383-008-2284-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress profile in the post-operative patients with biliary atresia

Abstract: The post-operative patients with BA were under increased oxidative stress, even if their liver dysfunction was mild without jaundice. Antioxidant therapy might be necessary to decrease of oxidative stress in the post-operative patients with BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Early-stage BA is associated with augmented oxidative DNA, mtDNA damage, and a decrease in mitochondrial copy number relative to that observed in late-stage BA. Our study was in accordance with Asakawa's which described that postoperative patients with BA were under increased oxidative stress [ 17 ]. Our report also proved that the oxidative stress increased more in BA before Kasai operation than after the operation and both are higher than the normal control [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Early-stage BA is associated with augmented oxidative DNA, mtDNA damage, and a decrease in mitochondrial copy number relative to that observed in late-stage BA. Our study was in accordance with Asakawa's which described that postoperative patients with BA were under increased oxidative stress [ 17 ]. Our report also proved that the oxidative stress increased more in BA before Kasai operation than after the operation and both are higher than the normal control [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, no study has evaluated the benefit of liver transplantation (LT) in BA patients in terms of oxidants/antioxidants. Our hypothesis is that if antioxidant levels are increased after LT [ 2 , 10 , 16 , 17 ], then the administration of antioxidants is needed in those cases who hesitate to receive LT or in cases where a liver graft is not available from donors. Therefore, our aim was to study the oxidative status in children with BA by examining the malondialdehyde (MDA) and antioxidant enzyme levels as well as mitochondrial copy numbers.…”
Section: Introductionmentioning
confidence: 99%
“…active oxygen species caused by chronic inflammation may lead to tissue injury and disease progression (17). In many BA patients, Kasai's hepatic portoenterostomy fails to resolve upregulation of oxidative stress, even in cases of mild liver dysfunction without jaundice (18). The aforementioned finding suggests that antioxidant therapy may be necessary for the treatment of BA patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that postoperative patients with BA were under severe oxidative stress, even with mild liver dysfunction without jaundice [13,21]. Oxidative stress results in the progression of cholestatic disease, while antioxidant therapy reduces cholestasis [13].…”
Section: Nt-group×40 T-group×40mentioning
confidence: 99%